Quercus ilex leaf as a functional ingredient: polyphenolic profile and antioxidant activity throughout simulated gastrointestinal digestion and antimicrobial activity - Sánchez-Gutiérrez, Mónica (2022)
Quercus ilex leaf constitute a rich source of bioactive compounds, especially phenolic compounds, with health and technological properties. In this study, the influence of in vitro gastrointestinal digestion on the bioaccessibility and bioactivity of phenolic compounds from ground leaf (GL) and leaf powder extract (PE) was evaluated for the first time. The GL showed an increase in antioxidant capacity, total phenolic content and individual phenolic compounds identified in the oral and gastric phase, decreasing in the intestinal and absorption (dialysis) phases, while PE showed a slight decrease in the oral and gastric phase and a more pronounced reduction in the last phases. Although the content of phenolic compounds and the antioxidant capacity were higher in the initial PE, the bioaccessibility (55.27% in GL vs. 34.23% in PE) and the recovery in the last step of the gastrointestinal tract in the colon-available fraction (29.24% in GL vs. 27.90% in PE) were higher in GL. The PE showed high antimicrobial activity against Escherichia coli, Listeria monocytogenes, Salmonella Typhimurium, Yersinia enterocolitica and Staphylococcus aureus, showing minimum inhibitory concentration values between 1 and 5 mg/mL. These results showed the complexity and richness of Q. ilex PE and GL in phenolics with high antioxidant and antimicrobial activity, underlining their use as a source of biofunctional compounds for the development of novel food additives and nutraceuticals.